2021
DOI: 10.1161/circinterventions.120.009879
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay, Infarct Size, and Microvascular Obstruction After Primary Percutaneous Coronary Intervention for ST-Segment–Elevation Myocardial Infarction

Abstract: Background : Symptom-to-balloon time (SBT) and door-to-balloon time (DBT) are both considered important metrics in patients undergoing primary percutaneous coronary intervention (pPCI) for ST-segment elevation myocardial infarction (STEMI). We sought to assess the relationship of SBT and DBT with infarct size and microvascular obstruction (MVO) after pPCI. Methods : Individual patient data for 3115 STEMI patients undergoing pPCI in 10 randomized trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Times to hospital presentation and first door-to-balloon times were strikingly prolonged, with a dramatic adverse impact on mortality and rates of cardiogenic shock. These data reinforce both dramatically and tragically the time-honoured concept of "time is muscle" 1,8,17 .…”
Section: Article See Page 27supporting
confidence: 62%
“…Times to hospital presentation and first door-to-balloon times were strikingly prolonged, with a dramatic adverse impact on mortality and rates of cardiogenic shock. These data reinforce both dramatically and tragically the time-honoured concept of "time is muscle" 1,8,17 .…”
Section: Article See Page 27supporting
confidence: 62%
“…We should collect routine data on "symptomto-balloon" (STB) time as this reflects the total ischaemic time and had been shown to correlate better with infarct size and left ventricular ejection fraction compared to DTB time. 17 Importantly, the STB time incorporates a patient's dimension into the quality matrix as it includes the time from symptom onset to first medical contact (the "patient delay") and reflects the success of our public educational efforts. The trends of both DTB time and STB time should be monitored in a national STEMI registry with steps taken to identify and address system and non-system related delays.…”
mentioning
confidence: 99%
“…Shiomi et al [ 18 ] also found that AMI patients with a short SBT (< 3 h) had a lower risk of mortality and heart failure than those with a long SBT (> 3 h), but patients with DBT > 90 min and those with DBT < 90 min had a similar risk of mortality and heart failure; only when SBT < 120 min, the risk of mortality and heart failure in AMI patients with DBT < 90 min was reduced. It suggested that SBT can better reflect the degree of myocardial injury and necrosis than DBT, thereby affecting the outcomes of patients, as suggested by more recent studies [ 14 , 16 , 20 ]. Like these studies, the present study revealed that with the prolongation of SBT, the risk of in-hospital mortality in AMI patients with EF < 50% was increased, but there was no increase in the risk of mortality in AMI patients with EF ≥ 50%, which has not been observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors mentioned above, SDT represents the time during which the patient is without medical care and during which damage is uncontrolled, without specific treatments at all, and it is associated with the prognosis of PCI [ 14 , 16 ]. On the other hand, the door-to-balloon time (DBT) represents when a patient is monitored and might receive medical treatments, but definitive treatment has not yet been undertaken; it is positively associated with the patient’s mortality [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation